Economic Cognitions Among Older Adults: Parental Socialization Predicts Financial Planning for Retirement - Palaci, Francisco; Jiménez, Irene; Topa, Gabriela (Frontiers in Aging Neuroscience, 2017)
Drawing on the model on financial planning for retirement (FPR), the aim of this work is to explore how parental economic socialization both directly and indirectly affects financial planning for retirement (FPR) through the mediation of financial literacy, financial planning decisions, and financial management. Data from a sample of 280 participants aged between 45 and 63 years were used. The results show that parental economic socialization directly and indirectly influences FPR. Moreover, parental economic behavior acts as a positive model for the development of financial literacy and skills and for decisions about FPR. All the variables increased the explained variance of FPR. Lastly, we discuss the process by which parental economic socialization is positively related to financial literacy and skills that impact on FPR, indicating some implications and future lines of research.